2007
DOI: 10.1373/clinchem.2006.076364
|View full text |Cite
|
Sign up to set email alerts
|

Human Plasma ATP Concentration

Abstract: Background: Human plasma ATP concentration is reported in many studies as roughly 1000 nmol/L. The present study tested the hypothesis that the measured plasma ATP concentration is lower if ATP release from formed blood elements is inhibited during blood sample processing. A second hypothesis was that pretreatment with aspirin to inhibit platelets would reduce the measured plasma concentration of ATP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
166
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(178 citation statements)
references
References 33 publications
8
166
0
Order By: Relevance
“…To account for ATP from red blood cell (RBC) haemolysis, a correction curve was set up as outlined previously (Gorman et al . 2007). The linear regression line of lysed RBC [ATP] (in nanomoles per litre) was plotted against the [Hb] (in milligrams per decilitre), with the relationship y = 4.61 x  − 4.79 and R 2 = 0.99.…”
Section: Methodsmentioning
confidence: 99%
“…To account for ATP from red blood cell (RBC) haemolysis, a correction curve was set up as outlined previously (Gorman et al . 2007). The linear regression line of lysed RBC [ATP] (in nanomoles per litre) was plotted against the [Hb] (in milligrams per decilitre), with the relationship y = 4.61 x  − 4.79 and R 2 = 0.99.…”
Section: Methodsmentioning
confidence: 99%
“…Supernatants of apoptotic cells released concentrations of 100-200 nM ATP and UTP during cell death. 41,42 Studies have shown that resting ATP plasma levels are~28 nM, 73 indicating that the release of ATP from apoptotic cells is significant compared with physiological concentrations. Not surprisingly, the EC 50 for many purinergic P2Y receptors are below 1 μM, A list of knock-out mice of proteins linked to specific find-me signal release or recognition.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…As the 'molecular unit of currency' of intracellular energy transfer, ATP transports chemical energy within cells to support metabolism 22 . ATP is present in low concentrations (o0.4 mM) in the extracellular environment, but is relatively concentrated within the intracellular cytosol (1-10 mM) [23][24][25][26] . Within cells, ATP provides energy to the cellular metabolism by breaking a phosphoanhydride bond.…”
mentioning
confidence: 99%
“…A maximum quenching efficacy was achieved when the molar ratio of duplex to Dox was 0.5. To investigate the ATP-responsive characteristics of the duplex, Dox/Duplex was incubated at 0.4 mM and 4 mM ATP concentrations, which represent the typical ATP level in the extracellular fluid and intracellular cytosol, respectively [23][24][25][26] . The dissociation of Dox/Duplex leads to the release of Dox, which can be estimated by detecting the recovery of the Dox fluorescence.…”
mentioning
confidence: 99%